Use of FACTS devices to maximize total transfer capability - Low, Chin Keat. (2009)
FACTS device such as Unified Power Flow Controller (UPFC) which has the capability to manipulate the power flow, is a useful device in controlling the power transfer from one bus to another. The effects of FACTS device on an electric power system network have been studied and presented. Investigations of optimal location of FACTS device where the total transfer capability is maximized were also conducted in this project and were documented in this report. The project analysis was performed using SimPowerSystem block set by MathWorks SIMULINK, a simulation package. A 5-bus system and a 14-bus system are adopted and modeled for simulation purposes. In this project, UPFC is selected as the FACTS device in the simulation. However, not all available functions of UPFC are used in these studies. Only the voltage injection function is tested in this project. The optimal allocation of UPFC in the 14-bus system is done through an analytical heuristic method. Background research on UPFC and TTC is also presented in this report.